Developing e-Book of Reading for Intensive Course in Virtual Classroom: Students’ Need Analysis - Elanneri Karani; Wahyuningsih Usadiati; Susanti; Sulamit Syeba; Otniel (The Study Program of English Education of Palangka Raya University, 2022)
This research clarifies the demands of students through need analysis concerning the content of e-book of reading for Intensive Course in virtual classroom, and the questionnaire was distributed to one hundred and twelve (112) students of English Study Program of FKIP University of Palangka Raya to explore the necessity. The results showed that most students require: first, reading texts as instructional materials which are accompanied by English grammar and English expressions to lead students to expose both oral and written English in daily life communication with other people using ICT (100%). Second, reading texts consist of 200-250 words (87.50%) which covered the topics of daily life and Dayak culture themes (.90%). Third, reading activity is to do reading a text and looking for detailed information (88.39%), and speaking activity is to discuss the exercises and tasks with peers (88.39%). Forth, writing input is about the explanation of the sentence structure used in the text, and writing activity that led them doing writing practice to write a text similar to the example given using their own sentence (82.84%). Fifth, learning activity on vocabulary and grammar cover pairing words with their meaning (89.28%), and write sentences according to the given pattern (100%). Last, the lecturer’s role acts as motivator and learners’ role are as responsive participants, and setting takes in virtual classroom or online learning. These signify student’s needs most which are as the basis for designing and developing e-book later.